(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
A new species of Paralecanopsis (Homoptera Coccoidea Coccidae) collected on Ammophila littoralis in north-eastern ltaly (province of Venice), is described and illustrated. The description of the crawler is also given. An identification key of species of Paralecanopsis is provided.